THE PEDAGOGICAL NOVEL IN THE RUSSIAN CHILDREN LITERATURE OF THE SECOND THIRD OF THE XX CENTURY - Meskin, V.A.; Zolotukhina, A.V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Literaturovedenie, zhurnalistika, 2017)
The article analyzes the formal-substantive components of the pedagogical novels in Russian literature of the XX century - “The Republic SHKID” by G. Belykh and L. Panteleev, “Pedagogical poem” by A. Makarenko, “School of Dostoevsky” V.N. Soroky-Rosinskiy. The author points to an implicit dialogue between these writers, with the necessity makes the excursions to the more remote past of the Russian literature, to the history and development of pedagogy, discusses about the causes and forms of interaction between pedagogy and literature for children. The subjective and objective preconditions of the formation of different author’s aesthetic and pedagogical concepts are identified.